2019
DOI: 10.1021/jacs.9b05063
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Activated PEGylated Conditional Aptamer/Antibody for Cancer Imaging with Improved Specificity

Abstract: Aptamers and antibodies, as molecular recognition probes, play critical roles in cancer diagnosis and therapy. However, their recognition ability is based on target overexpression in disease cells, not target exclusivity, which can cause on-target off-tumor effects. To address the limitation, we herein report a novel strategy to develop a conditional aptamer conjugate which recognizes its cell surface target, but only after selective activation, as determined by characteristics of the disease microenvironment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 35 publications
0
80
0
Order By: Relevance
“…The easy and reproducible manufacturing of aptamers combined with their composition that supports a plethora of chemical modifications allowing different conjugation chemistries renders them ideal molecular recognition probes for setting advanced anti-cancer strategies. Recently, Tan's group, in order to ameliorate the aptamers performance toward an efficacious targeted cancer therapy, developed a strategy to confine the aptamer's action solely to cancer cells while sparing normal cells, a crucial need when the aptamer's target is preferentially but not exclusively expressed in tumors [27]. They conjugated the aptamer with PEG5000-azobenzene-NHS, which acts as a caging moiety preventing aptamer-target recognition.…”
Section: Highlighted By Laura Cerchiamentioning
confidence: 99%
“…The easy and reproducible manufacturing of aptamers combined with their composition that supports a plethora of chemical modifications allowing different conjugation chemistries renders them ideal molecular recognition probes for setting advanced anti-cancer strategies. Recently, Tan's group, in order to ameliorate the aptamers performance toward an efficacious targeted cancer therapy, developed a strategy to confine the aptamer's action solely to cancer cells while sparing normal cells, a crucial need when the aptamer's target is preferentially but not exclusively expressed in tumors [27]. They conjugated the aptamer with PEG5000-azobenzene-NHS, which acts as a caging moiety preventing aptamer-target recognition.…”
Section: Highlighted By Laura Cerchiamentioning
confidence: 99%
“…To exploit these characteristics of the TME, antibodies have been engineered to bind preferentially at low pH or to bind only in the presence of aptamers activated under hypoxic conditions. [35][36][37] Other groups have designed proteaseactivated, bispecific T cell engagers either using masks attached via protease-cleavable linkers to block one or both of the antibody binding sites or employing protein domain complementation and Boolean logic gating to ensure bispecific activation only in the presence of two different tumor antigens. [38][39][40] The approach taken in this study was to separate the active domains of the T cell binding site from each other such that CD3 binding by the prodrug is impaired, and to use the functional tumor-targeting domains in the bispecific to accumulate these molecules on the surface of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…To exploit these characteristics of the TME, antibodies have been engineered to bind preferentially at low pH or to bind only in the presence of aptamers activated under hypoxic conditions. 35 - 37 Other groups have designed protease-activated, bispecific T cell engagers either using masks attached via protease-cleavable linkers to block one or both of the antibody binding sites or employing protein domain complementation and Boolean logic gating to ensure bispecific activation only in the presence of two different tumor antigens. 38 - 40 …”
Section: Introductionmentioning
confidence: 99%
“…Therapies that are originally inert but sensitive to hypoxia may provide tumor-specificity. Taking advantage of hypoxia in solid tumors, many efforts have been devoted to develop tumor-targeted therapeutic or imaging agents [7][8][9][10][11][12][13][14][15][16] . Nagano and Urano et al first reported that the azo group is sensitive toward hypoxia and may be employed to design fluorogenic probes for the detection of hypoxia 17 .…”
mentioning
confidence: 99%
“…Furthermore, they used the azo group as a quencher to design hypoxia-activated photosensitizers 12 . Recently, the groups of Tan, Fang, and Zhao collaborated to successfully design a hypoxia-activated aptamer for cancer imaging with improved specificity 13 . Based on hypoxia, Pu et al successfully activated a prodrug of the chemotherapeutic drug Br-IPM 14 .…”
mentioning
confidence: 99%